A Two-Step Nonstop-and-Go Phase Compensation Method for Spaceborne SAR With High-Resolution High-Squint-Angle and Wide-Swath - Yifan Wu; Lijia Huang; Bingchen Zhang; Lihua Zhong; Di Yin; Dadi Meng; Yuxin Hu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Current signal processing for synthetic aperture radar (SAR) cannot satisfy the requirements for high resolution, high squint angle, and wide swath due to the limitations of the traditional stop-and-go model. This model does not take into account the continuous motion between the satellite and the ground, leading to incomplete compensation for the corresponding phase. To address this issue, we first introduce an accurate range equation (ARE) based on the continuous satellite and ground motion, which allows for more precise slant range calculations. Second, we derive the point target spectrum according to the ARE, revealing additional phase components not considered in the traditional stop-and-go model. Third, we propose an advanced two-step processing algorithm to compensate for phase errors due to nonstop-and-go continuous motion. In the first-step processing, we eliminate range-independent components in the two-dimensional frequency domain. In the second-step processing, we compensate for residual phase errors related to range and azimuth frequency in the range-Doppler domain. We verified the proposed compensation method through simulation and compared it with the two-step compensation method used in high-resolution SAR data processing. Experimental results show that we provide an effective compensation method for high-resolution, high-squint-angle, wide-swath spaceborne SAR, which can correct azimuth shifts and solve the problem of defocusing at the edges of large scenes.